Intramolecular phosphacyclization: polyaromatic phosphonium p-heterocycles with wide-tuning optical properties - Belyaev, Andrei; Chen, Yi-Ting; Liu, Zong-Ying; Hindenberg, Philip; Wu, Cheng-Ham; Chou, Pi‐Tai; Romero-Nieto, Carlos; Koshevoy, Igor O. (Chemistry - a European journal, 2019)
Rationally designed cationic phospha-polyaromatic fluorophores were prepared through intramolecular cyclization of the tertiary ortho-(acene)phenylene-phosphines mediated by CuII triflate. As a result of phosphorus quaternization, heterocyclic phosphonium salts 1 c-3 c, derived from naphthalene, phenanthrene, and anthracene cores, exhibited very intense blue to green fluorescence (Φem=0.38-0.99) and high photostability in aqueous medium. The structure-emission relationship was further investigated by tailoring the electron-donating functions to the anthracene moiety to give dyes 4 c-6 c with charge-transfer character. The latter significantly decreases the emission energy to reach near-IR region. Thus, the intramolecular phosphacyclization renders an ultra-wide tuning of fluorescence from 420 nm (1 c) to 780 nm (6 c) in solution, extended to 825 nm for 6 c in the solid state with quantum efficiency of approximately 0.07. The physical behavior of these new dyes was studied spectroscopically, crystallographically, and electrochemically, whereas computational analysis was used to correlate the experimental data with molecular electronic structures. The excellent stability, water solubility, and attractive photophysical characteristics make these phosphonium heterocycles powerful tools in cell imaging.
Gesehen am 16.10.2019